INSTITUTIONAL SUPPORT FOR BIOGAS ENTERPRISES – THE LOCAL PERSPECTIVE - Chodkowska-Miszczuk, Justyna (Quaestiones Geographicae, 2019)
Institutional support, reflected not only in legislative solutions, but also in external funding as a means of financial support, is of strategic importance for the success of new power investments, the guarantee of energy security of individual areas, and the socio-economic development of the region where new energy enterprises are located. The present study aims to follow the external funding of biogas investments carried out in Poland, both in the aspect of legal regulations, and the offered co-financing of biogas projects. Considering that biogas enterprises are located and operate in specific places and local systems, the present research problem is tackled from the perspective of the functioning of biogas plants in the local environment. The success of biogas projects and the entire energy transformation process depends, on the one hand, on the harmonisation of activities at the central, national level and, on the other hand, on taking into account the specific socio-economic features that characterise the location of the biogas plant. Therefore, providing comprehensive institutional support for investment for biogas enterprises requires equipping local institutions, including local authorities, with appropriate instruments to shape and monitor the agricultural biogas market at the local level.